Techno-Economic Analysis in The Production of Copper Nanoparticles with Chemical Reduction Methods using L-Ascorbic Acid - Rahmahani Alfathia Fadhilah; Muhammad Roil Bilad2 (Indonesian Journal of Digital Business, 2022)
Copper  nanoparticles  (Cu-NPs)  are  a  type  of  nanoparticles with various industrial applications. The synthesis of copper nanoparticles  by  the  chemical  reduction  method  is environmentally  friendly,  simple,  and  produces  better nanoparticles compared to other methods. This study aims to determine the feasibility of a Cu nanoparticle manufacturing project through a chemical reduction method using L-ascorbic acid on an industrial scale and evaluate it from an engineering and  economic  perspective.  Technical  analysis  is  carried  out using  a  simple  balance  sheet  analysis  while  the  economic evaluation is carried out using several economic parameters, such as Payback Period (PBP), Break-even Point (BEP), and Cumulative  Net  Present  Value  (CNPV).  The  carried-out analysis  is  supported  by  using  data  taken  based  on  the availability of tools on online shopping websites. The results of the study show that this project is profitable and feasible to run with the anticipation of taxes and sales. This research is expected  to  provide  an  industrial  scale  representation  of  the economic  evaluation  and  plan  of  the  production  of  Cu nanoparticles  by  chemical  reduction  method  using  L-Ascorbic Acid.